Pengaruh Earnings Per Share (EPS), Price Earnings Ratio (PER), & Price Book Value (PBV) terhadap Harga Saham Perusahaan Farmasi yang terdaftar di BEI Periode 2016-2020 - Afrianita, Nina; Kamaludin, Faesal (Jurnal Indonesia Sosial Sains, 2022)
This study aims to test the influence of Earnings Per Share (EPS), Price Earnings Ratio (PER), and Price Book Value (PBV) on Stock Prices. The population of this study is pharmaceutical sector companies registered in IDX for the period 2016-2020. The population obtained is 10 companies and after the sample selection process with purposive sampling method, obtained 8 companies. The data source is obtained from the annual financial statements of pharmaceutical companies registered with IDX for the period 2016-2020. Data analysis method using data regression panel analysis with the help of Eviews 10 software application. The results showed partially variable Earnings Per Share (EPS), and Price Book Value (PBV) had a significant effect on the Share Price. While the Price Earnings Ratio (PER) has no significant influence on the Share Price. Simultaneously variable Earnings Per Share (EPS), Price Earnings Ratio (PER), and Price Book Value (PBV) affect the Share Price of pharmaceutical sector companies listed on IDX for the period 2016-2020 of 28.4%.